A discretely explosive text: Ideology and ideological state apparatuses - Almeida, Lúcio Flávio Rodrigues de (Pontifícia Universidade Católica de São Paulo, 2014)
The objective of this paper is to highlight the deeply subversive character, on both the theoretical and political-ideological planes, of Louis Althusser’s article “Ideology and Ideological State Apparatuses.” The analysis proceeds by examining some continuities in the Althusserian approach to ideology and, within that approach, relevant innovations. Among the latter the one that is emphasized consists of a change in central focus from the epistemological dimension to the social function of ideology.